Effect of durotomy on functional outcome of dogs with type I thoracolumbar disc extrusion and absent deep pain perception - Loughin, C. A.; Dewey, C. W.; Ringwood, P. B.; Pettigrew, R. W.; Kent, M.; Budsberg, S. C. (Veterinary and Comparative Orthopaedics and Traumatology, 2005)
Spinal cord durotomy is performed as a diagnostic aid in determining spinal cord structural integrity, and this may be useful as an indicator of prognosis in cases with loss of deep pain perception (DPP). It has been suggested that a durotomy may relieve intramedullary compression but there is some debate about the therapeutic value. The purpose of this study was to compare ambulatory outcome of dogs that had loss of DPP treated with hemilaminectomy with durotomy versus hemilaminectomy without durotomy. Medical records of 81 dogs diagnosed with type I thoracolumbar IVD were reviewed. Dogs were included in the study if DPP was absent upon initial neurological examination and surgical decompression via hemilaminectomy was performed. Of the 81 cases, 48 were included in this study. The number of dogs that recovered ambulatory function were compared between durotomy and nondurotomy groups with a chi-squared test (p<0.05). No differences were found. The findings of this study suggest that durotomy is useful as a diagnostic modality and that performing a durotomy does not significantly affect post-operative recovery of voluntary motor function.
Keywords: Durotomy; deep pain perception; hemilaminectomy; thoracolumbar